Problemy z gospodarką wodno-ściekową na przykładzie gminy Kłobuck - Rozpondek, Patrycja; Skibiński, Andrzej; Rączaszek, Andrzej (The problem of water economics and water sewage disposal in Kłobuck commune, 2006)
Kłobuck is situated in the Northern part of the Silesian province, on Cracow-Wieluń Upland, in the valley of Biala Oksza river (the tributary of Liswarta). Kłobuck lies 90 km away from Katowice, the capital of province, and 18 km away from Częstochowa. Commune Kłobuck possesses well developed water-pipe network. The sewage system exists in the region of the Kłobuck city, which is operated by the mechanically - biological treatment plant along with the dewatering of the sludge station, built in 1997. The aim of the article is to present the problems connected with water economics and water sewage disposal in Kłobuck commune.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 34-41